Progress in on-line, at-line, and in-line coupling of sample treatment with capillary and microchip electrophoresis over the past 10 years: A review - Tůma, Petr (Analytica chimica acta, 2023)
The review presents an evaluation of the development of on-line, at-line and in-line sample treatment coupled with capillary and microchip electrophoresis over the last 10 years. In the first part, it describes different types of flow-gating interfaces (FGI) such as cross-FGI, coaxial-FGI, sheet-flow-FGI, and air-assisted-FGI and their fabrication using molding into polydimethylsiloxane and commercially available fittings. The second part deals with the coupling of capillary and microchip electrophoresis with microdialysis, solid-phase, liquid-phase, and membrane based extraction techniques. It mainly focuses on modern techniques such as extraction across supported liquid membrane, electroextraction, single drop microextraction, head space microextraction, and microdialysis with high spatial and temporal resolution. Finally, the design of sequential electrophoretic analysers and fabrication of SPE microcartridges with monolithic and molecularly imprinted polymeric sorbents are discussed. Applications include the monitoring of metabolites, neurotransmitters, peptides and proteins in body fluids and tissues to study processes in living organisms, as well as the monitoring of nutrients, minerals and waste compounds in food, natural and wastewater.
Keywords: elektroforéza kapilární; mikrodialýza; elektroforéza mikročipová; Electrophoresis, Microchip; Liquid-phase extraction; Capillary electrophoresis; Solid-phase extraction; On-line coupling; Flow-gating interface; Electromembrane extraction; Sequential analysis; Microdialysis; Microchip electrophoresis; Electrophoresis, Capillary